Numerical Simulation of Unsaturated Soil Water Flow from a Trickle Point System, Considering Evaporation and Root Water Uptake - Khalil, Lina Ali; Abid, Maysoon Basheer (Al-Khwarizmi Engineering Journal, 2018)
This research was carried out to study the effect of plants on the wetted area for two soil types in Iraq and predict an equation to determine the wetted radius and depth for two different soil types cultivated with different types of plants, the wetting patterns for the soils were predicted at every thirty minute for a total irrigation time equal to 3 hr. Five defferent discharges of emitter and five initial volumetric soil moisture contents were used ranged between field capacity and wilting point were utilized to simulate the wetting patterns. The simulation of the water flow from a single point emitter was completed by utilized HYDRUS-2D/3D software, version 2.05. Two methods were used in developing equations to predict the domains of the wetting pattern. The principal strategy manages each soil independently and includes plotting, fitting, and communicating relevant connections for wetted zone and profundity, maximum error did not exceed 31.2%, modeling efficiency did not less 0.95, and root mean square error did not surpass 1.43 cm. The second strategy additionally treated each soil independently yet used electronic programming that uses different relapse methods for wetted territory and profundity, the maximum error did not exceed 15.64 %, modeling efficiency did not less 0.98, and root mean square error did not surpass 1.18 cm. a field test was directed to quantify the wetted radius to check the outcome acquired by the software HYDRUS-2D, contrast the estimation and the reproduced by the software. The after effects of the conditions to express the wetted radius and depth regarding the time of water system, producer release, and initial soil moisture content were general and can be utilized with great precision.